Speed profile estimation using license plate recognition data - Mo, Baichuan; Li, Ruimin; Zhan, Xianyuan (Transportation research. Part C, Emerging technologies, 2017)
•A systematic LPR data-mending method is proposed.•Propose a modified car-following model corresponding to LPR data characteristics.•The speed profile of vehicles on road segments is estimated using proposed model.•The proposed model is validated by a field experiment.•The model can fully capture the pattern of ground truth speed profile. Vehicle speed profile is a fundamental data support for calculating vehicular emission using the micro-emission model. However, achieving accuracy and breadth for the speed profile estimation is difficult. This study proposes a new vehicle speed profile estimation model using license plate recognition (LPR) data. This model allows speed profile estimation of every individual vehicle between two consecutive intersections. A systematic LPR data-mending method is developed to infer the information of unmatched vehicles. Using the complete arrival and departure information as boundary conditions, a customized car-following model combined with dummy-overtaking hypothesis and boundary constraints is then applied to estimate the speed profile of vehicles. The proposed model is validated using ground truth speed information from a field experiment conducted in Langfang City in China. Results show that the model can fully capture the pattern of ground truth speed profile. A complementary model validation using the Next Generation Simulation dataset and a model application for calculating emissions are also conducted. The numerical results indicate the effectiveness of the proposed model in estimating vehicle speed profile and emissions.